Association Between Neuraxial Analgesia and Postpartum Opioid Use Following Vaginal Delivery. Issue 4 (December 2020) - Badreldin, N.; Grobman, W.A.; Yee, L.M.
Abstract : ( Am J Obstet Gynecol . 2020;222:278–279) While neuraxial analgesia is highly effective and the most common pain management strategy during labor, there is a lack of information on opioid consumption following vaginal delivery with neuraxial analgesia. This study aimed to investigate the association between intrapartum neuraxial analgesia for vaginal delivery and postpartum opioid use.